SOSIALISASI RUMAH SEHAT GUNA MENINGKATKAN PENGETAHUAN SERTA KESADARAN BAGI MASYARAKAT - Fitriani, Farida; Endriani, Ani; Maulana, Muhmmad Imam; Rayani, Dewi; Kurniawati, Wiwien (Fakultas Ilmu Pendidikan dan Psikologi, 2024)
This community service activity aims to provide knowledge, and increase public understanding and awareness in creating healthy, livable homes and realizing healthy and decent housing management. The method used in this service activity is socialization and in the form of healthy home assistance and evaluation of healthy home assistance. The target of this community service activity is the community of Gontoran Hamlet, Sesaot Village, Narmada, West Lombok. The hope of this service in Gontoran Hamlet, Sesaot Village, Narmada, West Lombok, is that the community will better understand the criteria or indicators for a healthy home, efforts to have a healthy home and the community will play an active role in creating a healthy home by keeping the area around the house more clean, in order to create a healthy family, to organize and improve the quality of good residential areas.